Determinants of Profitability of Insurance Companies in Nepal (Patan Prospective Journal, 2023)
The ability of a corporation to turn a profit from all of its business endeavors is expressed by its profitability. It demonstrates how well management uses all available resources to generate profit. This study attempts to investigate the determinants of profitability of insurance companies in Nepal. This study is based on secondary data of 15 sample insurance companies using convenient sampling and it covers the period 2016/17 to 2020/21 with 75 observations. The results of this study revealed that expense ratio, financial leverage, claim ratio and size of company have impact on profitability of the insurance companies in Nepal. Expense ratio and claim ratio have significant negative and financial leverage and size of company have positive impact on profitability of the insurance companies in Nepal. This study also revealed the insignificant effect of age on profitability of insurance companies.